2018
DOI: 10.1016/j.ultsonch.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Sonoluminescence and acoustic emission spectra at different stages of cavitation zone development

Abstract: The way in which a cavitation zone develops in a focused pulsed ultrasound field is studied in this work. Sonoluminescence (SL), total hydrophone output and cavitation noise spectra have been recorded across a gradual, smooth increase in applied voltage. It is shown that the cavitation zone passes through a number of stages of evolution, according to increasing ultrasound intensity, decreasing pulse period and increasing ultrasound pulse duration. Sonoluminescence is absent in the first phase and the hydrophon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
1
14
0
3
Order By: Relevance
“…In their work, the authors presented an intracellular cavitation mechanism to explain some US biological effects, from delicate and reversible bioeffects [71], to complete membrane disruption and irreversible cellular damage [72]. Moreover, in a previous work, we ourselves have shown that the cavitation zone passes through a number of stages of evolution and SL seems to develop accordingly [27]. In this scenario, it is not unreasonable to assume that the intracellular cavitation mechanism might also elicit an intracellular cavitation zone with different stages of evolution that are able to trigger our porphyrin compounds.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In their work, the authors presented an intracellular cavitation mechanism to explain some US biological effects, from delicate and reversible bioeffects [71], to complete membrane disruption and irreversible cellular damage [72]. Moreover, in a previous work, we ourselves have shown that the cavitation zone passes through a number of stages of evolution and SL seems to develop accordingly [27]. In this scenario, it is not unreasonable to assume that the intracellular cavitation mechanism might also elicit an intracellular cavitation zone with different stages of evolution that are able to trigger our porphyrin compounds.…”
Section: Discussionmentioning
confidence: 98%
“…For some researchers, acoustic cavitation is an extreme phenomenon that is responsible for generating excessive vibration, erosion, reduced hydraulic performance and structural damage [22], while, for others, it is seen as an enormous concentration of energy with a wide range of unexplored chemical and physical consequences [23,24]. In particular, the emission of SL [25][26][27] has been proposed as the pivotal trigger for the sonosensitiser-mediated generation of reactive oxygen species (ROS) in SDT [28,29]. This hypothesis was formulated because most of the chemical compounds used in SDT are also photosensitisers [14].…”
Section: Introductionmentioning
confidence: 99%
“…The previous literature generally believed that ultrasound induced sonosensitizers to produce 1 O 2 due to acoustic cavitation and sonoluminescence (53)(54)(55), but this often requires a higher sound intensity beyond diagnostic dose ultrasound. Ultrasound, as a kind of material vibration wave, can form phonons at the level of protein macromolecules and cause phonon-electron coupling (56).…”
Section: Discussionmentioning
confidence: 99%
“…The previous literature generally believed that ultrasound induced sonosensitizers to produce 1 O 2 owing to acoustic cavitation and sonoluminescence ( Dezhkunov et al., 2000 , 2018 ; Sazgarnia et al., 2013 ), but this often requires a higher sound intensity beyond diagnostic dose ultrasound. Ultrasound, as a kind of material vibration wave, can form phonons at the level of protein macromolecules and cause phonon-electron coupling ( Viani et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%